Dasar Hukum Penuntut Umum Mengajukan Kasasi Terhadap Putusan Lepas Dari Segala Tuntutan Hukum Dalam Perkara Penggelapan Dalam Jabatan Secara Berlanjut - Alfian Nanung Pradana (Sebelas Maret University, 2017)
The purpose of this research is to know the legal status of the public prosecutor in filing appeal against matters of embezzlement in Office continuously charged with Article 64 paragraph (1) Jo. Article 32 of the Criminal Code. This study discusses the embezzlement in Office continuously conducted Sharif Muda Siregar, S.E., West. The Act of the defendant that is several times has been taking money from the Treasurer of the school which should belong to the Foundation and use it for the benefit of outside Islamic College Foundation's interests rather than